Hybrid Neoliberalism: Implications for Sustainable Development. Issue 5 (4th May 2019) - Baldwin, Claudia; Marshall, Graham; Ross, Helen; Cavaye, Jim; Stephenson, Janet; Carter, Lyn; Freeman, Claire; Curtis, Allan; Syme, Geoff
Abstract: Neoliberalism is frequently blamed for challenges in achieving sustainable development; consequently some also question if sustainability is still a useful concept. Neoliberal influence on natural resource management has evolved over the last 30 years to a hybrid form that seeks to compensate for its negative social and environmental externalities. Through review of literature and critical analysis of three case studies of resource development in Australia and New Zealand, we argue that, in spite of modifications under hybrid approaches, neoliberalism still tests achievement of sustainability goals, due to privileging industry and shifting risk and costs to future generations, through inadequate regulation, neglect of public consultation, lack of transparency, and weak impact assessment. We suggest that while neoliberal approaches bring both benefits and disadvantages, sustainability principles must continue to be kept at the forefront of legislation, regulation and management.